Platelet Transfusion in Critical Care and Surgery: Evidence-Based Review of Contemporary Practice and Future Directions. Issue 5 (May 2017) - Etchill, Eric W.; Myers, Sara P.; Raval, Jay S.; Hassoune, Adnan; SenGupta, Anirban; Neal, Matthew D.
Abstract : ABSTRACT: Thrombocytopenia is prevalent in critical care, surgical, and trauma settings. Despite the fact that a significant proportion of these patients receive platelet transfusion during their hospital course, much work remains to be done with regard to development of platelet transfusion guidelines. Given the wide variety of platelet transfusion practices and the frequency with which patients present with thrombocytopenia, it is paramount to understand standards of care and to identify deficiencies that may exist. This review explores evidence and recommendations for platelet transfusion thresholds and practices in a variety of critical care and surgical settings with specific focus on the role of platelet transfusion in trauma, management and reversal of anticoagulation, and point of care laboratory assays. To this end, a literature review was performed utilizing PubMed and Cochrane Central Register of Controlled Trials to select 153 manuscripts that evaluate the current data supporting platelet transfusions in surgical and critical care populations. Advances in transfusion medicine and synthetic platelet substitutes that can be engineered for potential future applications will also be discussed.